FEATURES OF ECONOMIC ACTIVITIES OF MUNICIPAL ENTERPRISES RELATED TO WASTE - Timush, Iryna; Yastremska Оlena (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Goal: identifying the peculiarities of the economic activity of communal enterprises, for which activity in the field of waste management/waste management is the main one, forming proposals to eliminate the shortcomings of the legal regulation of such activity and improving the relevant legislation. Research methods: general (analysis, synthesis, comparison, induction, deduction) and special research methods (systemic-functional, formal-logical, formal-legal) are applied in combination. Results: it has been proven that today communal enterprises remain the main type of economic entities in the field of waste at the local level. Their business activities are mostly unprofitable and subsidized. Local self-government bodies and communal enterprises themselves, whose main activity is related to waste, do not contribute to the competition of business entities in the field of waste. The new Law of Ukraine «On Waste Management» preserves the risks of negative influence of local self-government bodies on the competition of business entities in the field of waste. This normative legal act specifies the rights and obligations of various business entities in the field of waste management, giving a prominent place to the utility company – the administrator of household waste management services. The priority of the activities of municipal enterprises in the field of collection, removal, utilization and processing, disposal of waste is substantiated, provided that the system of control over their activities is improved, especially by the Antimonopoly Committee of Ukraine. It is necessary to form a coordinated system of normative legal acts of different levels. Discussion: feasibility of municipalization of waste disposal services, regulation of tariffs for household waste, which does not contribute to the profitability of enterprises, types and volumes of incentives for communal enterprises operating in the field of waste, implementation of public-private partnerships, as well as partnerships between territorial communities and subjects of private entrepreneurship sectors of the economy to solve waste problems.